Numerical Simulations of 122 mm M-21OF Missile Fragments Propulsion - Wojciech IMBIEROWICZ (Badania numeryczne procesu napędzania odłamków 122 mm rakietowego pocisku M-21OF, 2024)
This paper presents numerical simulations of 122 mm M-21OF rocket fragments propulsion. A simplified geometry of the rocket was constructed and analysed with two main numerical FE approaches: a mesh-based lagrangian-eulerian FSI method and a coupled meshless SPH–lagrangian approach. The resulting fragment velocities were compared with those obtained from an analytical approach (Gurney formula). The shell fragmentation process was also successfully depicted. Both numerical approaches differed from the analytical velocity results to a comparable degree. Considering that the Gurney energy of a high-explosive is obtained from cylinder expansion tests, results obtained with the Gurney method can be treated as a reference point and validation method for natural fragmentation warhead models.
Keywords: Balistyka zewnętrzna odłamków pocisku rakietowego